1992
DOI: 10.1002/hep.1840150429
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular Liver Biopsy

Abstract: Although transjugular liver biopsy requires the availability of trained personnel, takes more time than percutaneous biopsy and is moderately expensive, it is a safe alternative technique for obtaining adequate liver tissue for diagnosis in special clinical situations. The usual indications for transjugular rather than percutaneous liver biopsy are (a) coagulation disorder (prothrombin time greater than 3 sec over control value and/or platelet count less than 60,000/cm3), (b) massive ascites and (c) desire to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
2
10

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 24 publications
3
80
2
10
Order By: Relevance
“…In a review carried out by McAFEE et al (25) , an average of 3.5 triads (± 3.5 SD) is reported, but the type of needle employed is not specified. KARDACHE et al (20) reported eight or more portal triads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review carried out by McAFEE et al (25) , an average of 3.5 triads (± 3.5 SD) is reported, but the type of needle employed is not specified. KARDACHE et al (20) reported eight or more portal triads.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive fragmentation of liver specimens was observed even after the change to a reversed bevel needle and the addition of an inner stylet (10,13,15,23) . A modified version of the percutaneous Vim-Silverman side-cutting needle -the trucut needle -has been proposed for TJLB with the aim of providing larger and less fragmented specimens (7,16,25) . An automated trucut needle, the Quick-Core needle system has also been proposed, and its success rate of histological diagnosis seems to be higher than the modified aspiration Ross needle in patients with suspicion of chronic liver diseases (2,9,12,18,19,20,27) .…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…9,19,20 The transjugular approach offers other advantages as well, including the ability to perform imaging studies of the hepatic venous system and determining intrahepatic pressures. 9,12,21 While this procedure has been used to evaluate hepatic dysfunction in adult HSCT patients, studies in pediatric HSCT recipients are limited. Of the five studies reporting on the success of this approach in children, [22][23][24][25][26] only two included HSCT patients.…”
Section: Discussionmentioning
confidence: 99%
“…23,25 These studies concluded that the transjugular liver biopsies are safe and effective in the pediatric population, but this approach also has significant disadvantages including the need for highly skilled personnel, increased procedure time, and concerns relative to inadequate sample size for histologic examination. 12 Laparoscopy is a widely used diagnostic and therapeutic tool, and liver biopsy using this approach has proven to be an effective means for evaluating hepatic dysfunction in adult patients with hematologic malignancies. Iqbal et al 27 reported on a series of 29 adults who were immunocompromised, thrombocytopenic, and often neutropenic following intensive cytotoxic therapy with or without HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation